Effect of comprehensive nursing interventions on relieving postoperative pain of breast cancer patients (乳腺肿瘤患者术后疼痛的护理干预研究) - LI Weijia (李唯佳); LI Yueru (李月茹); LI Ning (李宁); CAO Hongjing (曹红京) (中西医结合护理)
Objective To investigate the effect of comprehensive nursing interventions on relieving postoperative pain of patients after breast cancer surgery. Methods A total of 80 breast cancer patients were randomly divided into the study group and control group, with 40 cases in each group. All patients received routine nursing and pharmacologic treatment for postoperative pain, and those in the study group were given comprehensive interventions such as basic nursing, psychological nursing and positioning nursing. The degree of postoperative pain was measured by using Visual Analogue Scale (VAS), and patients’ satisfaction with nursing service was investigated by using a self-made questionnaire. Results The VAS score of the study group was significantly lower than that of the control group at 1 day, 3 days and 7 days after surgery(P＜0. 01). The satisfaction rate of the study group was higher than that of the control group, with a significant difference(P＜0. 01). Conclusion Comprehensive nursing interventions are effective to reduce the postoperative pain and improve the nursing satisfaction of patients after breast cancer surgery. (目的 探讨乳腺肿瘤患者术后疼痛的护理干预效果。方法 选取2020年6月—2022年12月医院收治的乳腺肿瘤患者80例为研究对象, 分为研究组(n=40)和对照组(n=40)。对照组采用常规护理和药物镇痛干预, 研究组在对照组基础上增加基础护理、心理护理、体位护理等综合护理干预措施。采用视觉模拟评分(VAS)评估患者术后疼痛, 采用自制量表对患者护理满意度进行评价。结果 研究组术后1 d、3 d和7 d的VAS评分低于对照组, 差异有统计学意义(P＜0. 01)。研究组护理满意度高于对照组, 差异有统计学意义(P＜0. 01)。结论 综合护理干预能进一步减轻乳腺肿瘤患者术后疼痛程度, 提升患者护理满意度。)